Strengthen students' sense of responsibility in learning PJOK through the TPSR model - Faisal, Muhammad; Maesaroh, Siti; Vai, Aref; Aspa, Agus Prima (Journal of Physical Education Health and Sport, 2023)
The complexity of issues surrounding character or morality has suddenly become a troubling thought with a personality or moral crisis characterized by an increase in violent crime, bullying, drug addiction, pornography and promiscuity that has become a pathology of society. The methodology used in this research is library research. The purpose of literature research is to use the information obtained to describe the content obtained or the information obtained. The data sources used come from research articles from various national and international sources that are published and can be downloaded on the internet such as Google Scholar, Scopus, Garuda, Sinta, Taylor and Francis using the PICO method. In some of the studies that have been discussed, there are similarities in the application of the Teaching Personal and Social Responsibility model in PJOK learning with the aim of producing and increasing individual and social responsibility. Based on the summary of the 15 posts, it can be concluded that the TPSR model is a suitable approach to increase students' individual and social responsibility in personality development in the context of PJOK subjects. By analyzing the literature sources, it can be concluded that the Teaching Personal and Social Responsibility (TPSR) model has proven effective in increasing students' personal and social responsibility. There are 15 articles or journals that document in detail the successful application of the TPSR model in Physical Education, Sports and Health (PJOK) education. Therefore, it can be suggested that this model can provide assistance in creating or increasing students' sense of personal and social responsibility in character development in the context of PJOK subjects.